STIMULASI EKSTRAK PROPOLIS PADA ODONTOBLAST LIKE CELLS YANG DIINDUKSI LACTOBACILLUS ACIDOPHILUS INAKTIF TERHADAP EKSPRESI TLR2 DAN TNFα - Ira Widjiastuti; Nadia Irnatari; Mandojo Rukmo (Faculty of Dentistry, Universitas Islam Sultan Agung, 2017)
Background: Lactobacillus acidophilus, Gram-positive bacterias that enterthe dentinal tissue during the carious process are suspected to inﬂuence the immune response in human dental pulp. Odontoblasts situated at the pulp dentin interface are the frst cells encountered by these bacteria and have an important role in this response. Lipoteichoic acid (LTA), a wall component of Gram-positive bacteria, triggered the activation of the odontoblasts. LTA upregulated the expression of its own receptor TLR2, as well as the production of proinﬂammatory cytokineTNFα. Propolis is a resinous material that holds a great potential as an antiinﬂammatory agent. Present studies have shown that propolis has a reduction eﬀect towards the proinﬂammatory cytokines expression and favor pulp healing.Purpose: To reveal the moleculer mechanism of propolis stimulation onodontoblast like cells, induced by inactive Lactobacillus acidophilus.Methods: This review was presented in odontoblasts like cells culture induced by inactive Lactobacillus acidophilus and exposed to propolis extract. Pulp cell culture isolated from human impacted thirds molar that has been extracted. Observation and measurement the expression of TLR2 and TNFα was processed by using immunocytochemistry (ICC) technic.Result: Data analysis with ANOVA test, a signifcant diﬀerence in every group(p<0,05) was present. The expression of TLR2 and TNFα were shown at lowlevel percentation on odontoblast like cells, induced by Lactobacillus acidophilus and propolis extract stimulation.Conclusion: Propolis extract stimulations lower the TLR2 and TNFα expression on odontoblast like cells, induced by inactive Lactobacillus acidophilus